Assessment and Evaluation of Different Machine Learning Algorithms for Predicting Student Performance - Alsariera Y.A.; Baashar Y.; Alkawsi G.; Mustafa A.; Alkahtani A.A.; Ali N. (Hindawi Limited, 2023)
Decision trees; Learning algorithms; Nearest neighbor search; Neural networks; Students; Support vector machines; Academic achievements; Effective tool; Key feature; Large volumes; Machine learning algorithms; Machine learning approaches; Student performance; Systematic searches; Tertiary institutions; Top qualities; Forecasting; algorithm; Bayes theorem; human; machine learning; student; support vector machine; Algorithms; Bayes Theorem; Humans; Machine Learning; Neural Networks, Computer; Students; Support Vector Machine